Pengolahan Air Sungai Sebagai Sumber Air Bersih Masyarakat Di Kawasan Pertanian Dengan Penyaringan Air Sederhana - Maksuk, Maksuk; Priyadi, Priyadi; Anwar, Khairil (LPPM Univ. Ibn Khaldun Bogor, 2022)
Sembadak Village is one of the villages located in Pemulutan District Ogan Ilir Regency has problems with the availability of clean water. The water used by the community comes from a tributary of the Ogan River is relatively cloudy. This condition can cause the risk of health problems, especially water-borne diseases such as dysentery, cholera, gastroenteritis, and other diseases. Villagers still use river water as a source of clean water for their daily needs, namely for bathing, washing, and other purposes. Although there is a Regional Clean Water Company in Pemulutan District, the community has not been able to access the water, and complaints from the community and community health center staff are still relatively cloudy. To overcome these problems, a water filtration system with a filtration method is applied to this community service activity. Water filtration with this filtration method uses several media namely silica sand, coconut shell activated charcoal, sponge, and nano filter to filter sediment particles. This sand filter is operated in an up-flow manner and then the overflow is fed into a gradual pipe filtration. The step-pipe filter consists of two 4 inch pipes containing shell charcoal, sand, and sponge. This system is designed with filter materials that are easy to find and simple system construction; it can be maintained, operated, and duplicated by the local community. The filtration system can reduce several parameters, including turbidity, iron and manganese level, and pH in raw water.